2020
DOI: 10.2337/dc19-2540
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure Variability and Risk of Heart Failure in ACCORD and the VADT

Abstract: Objective: Although blood pressure variability is increasingly appreciated as a risk factor for cardiovascular disease, its relationship with heart failure is less clear. We examined the relationship between blood pressure variability and risk of heart failure (HF) in two cohorts of type 2 diabetes participating in trials of glucose and/or other risk factor management. Research Design and Methods: Data were drawn from the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial and the Veterans Affairs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
4
21
1
1
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12] Our observations of a positive association between BP variability and risk of HF are consistent with the few studies conducted so far, although individuals without Type 2 diabetes were included in some of these reports. 5,12 Contrary to the extant studies, our study includes a variety of measures of BP variability, as well as a diverse multi-ethnic/racial sample of participants. 5 There are causal pathways that could explain the positive relation between long-term variability in BP and risk of HF in Type 2 diabetes.…”
Section: Discussionsupporting
confidence: 90%
“…[4][5][6][7][8][9][10][11][12] Our observations of a positive association between BP variability and risk of HF are consistent with the few studies conducted so far, although individuals without Type 2 diabetes were included in some of these reports. 5,12 Contrary to the extant studies, our study includes a variety of measures of BP variability, as well as a diverse multi-ethnic/racial sample of participants. 5 There are causal pathways that could explain the positive relation between long-term variability in BP and risk of HF in Type 2 diabetes.…”
Section: Discussionsupporting
confidence: 90%
“…The ASPREE trial also demonstrated a higher risk of HF events with higher SBP variability. In patients with type 2 diabetes from the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial and the Veterans Affairs Diabetes Trial (ADT), BP variability measured by SBP and DBP were both associated with increased risk of HF, even after adjusting for other risk factors and mean BP (9). The current study builds on these previous works to clarify that the MAP variability, similar to SBP or DBP variability, was also associated with the risks of HF and death.…”
Section: Discussionmentioning
confidence: 99%
“…The 2017 American College of Cardiology (ACC)/American Heart Association (AHA) (1) and 2018 European Society of Cardiology (ESC)/European Society of Hypertension (ESH) (2) blood pressure (BP) guideline recommends using a single measurement or the average of BP levels assessed over time to screen for and manage high BP in adults, while occasional BP increase or reduction has not been taken seriously by clinicians. Although fluctuation of BP is physiological (3), a growing number of clinical and observational studies have demonstrated that elevated BP variability contributes to the risk of cardiovascular disease (CVD) and death, independently of mean BP (4)(5)(6)(7)(8)(9)(10)(11)(12). Thus, BP variability has increasingly been recognized as a novel CVD risk factor that can provide more accurate estimates for the clinical outcomes in adults (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, pooled data from the ACCORD and VADT Trials have shown that both systolic and diastolic blood pressure variability can favor the development of heart failure in T2D, an effect likely mediated by dips, not elevations, of blood pressure [ 15 ].…”
Section: Variability Of Risk Factors and Diabetic Complicationsmentioning
confidence: 99%